APPLICATION OF NORMAN’S THREE LEVELS DESIGNTHEORY FOR ARTEFACT ANALYSIS OF CULTURAL RELATED DESIGN PROCESS - Cheng, Wean Ting; Musdi, Shanat (UNIMAS Publisher, 2020)
Culture always associate with human activity which could give an identity. Any culture that associate with materials and objects is an aid to the creation of lasting identities. The culture will suffer loss and extinction due to less attention and preservation. In reality, designers seem less to care in injecting the cultural value in their creation and facing hardship in translating a culture object into a product. Designing a product with a cultural element could emphasis its sentimental and commercial value in the global market. Therefore, this paper aims at proposing a design process framework on how culture can be employed to generate and create product. The proposed framework explains how a culture object can inspire designers to create a product with the intervention of Norman’s Three levels of Design theory. The Artefact Analysis and online survey are used to obtain the finding and creating a proof of concept that the proposed framework model capable to provide valuable references for designing a culture-inspired product. On the other hand, the local identity could be brought up globally through culture-inspired products.